Rapid response to mycophenolate mofetil in combination with romiplostim in a case of severe refractory immune thrombocytopenia post COVID‐19 vaccination - Snigdha Nutalapati (Wiley, 2021)
Abstract Vaccine mediated immune mediated thrombocytopenia (ITP) is exceedingly rare. We present a case of a young female who developed severe refractory ITP with multiple bleeding sites post second dose of COVID‐19 vaccination. She was treated with a combination of romiplostim and mycophenolate mofetil that resulted in rapid platelet count recovery.